2010
DOI: 10.1111/j.1551-2916.2010.03670.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Temperature and Nitrogen Flow Rate During the Carbothermic Synthesis of SiC/Si3N4 Nanocomposite Powder from Gel

Abstract: This research article explores the synthesis of SiC/Si 3 N 4 nanocomposite powder via a carbothermic reaction of silica xerogel under nitrogen atmosphere. The influence of both reaction temperature and nitrogen flow rate on the properties of the produced sample was thoroughly investigated. The results revealed that both reaction temperature and nitrogen flow rate played a very important role not only on the composition ratio of SiC/Si 3 N 4 in the finally produced sample but also on the morphology of both phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
3
6
0
Order By: Relevance
“…This may not be a surprise if one graphite particle can serve as nucleation sites for multiple SiC and Si 3 N 4 crystals. The present observation is consistent with the previous studies showing that Si 3 N 4 and SiC nucleate on the surface of carbon.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…This may not be a surprise if one graphite particle can serve as nucleation sites for multiple SiC and Si 3 N 4 crystals. The present observation is consistent with the previous studies showing that Si 3 N 4 and SiC nucleate on the surface of carbon.…”
Section: Resultssupporting
confidence: 94%
“…The formation of α‐Si 3 N 4 by carbothermal reduction and nitridation of silica has been reported to occur in two principal reaction steps. The first step consists of reduction of silicon dioxide to gaseous silicon monoxide species following either reactions or . Once the gaseous SiO species is formed, the silicon nitride particle nucleates on the surface of carbon and grows following reactions and .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All produced films are obviously show very interesting features of ultraviolet (UV) PL emission with high intensity bands centered at 331, 390, 420 and 480 nm when the samples are excited by a 354 nm light from Xe lamp at room temperature. The positions of these emission lines are consistent with that found in the early reported literatures for SiO 2 , SiOC, SiC, TiO 2 and TiOC phases, respectively [4,28,[32][33][34][35][36][37]. This observation is rather confirmed that these films are most probably a nanocomposite film of the Si\Ti\O\C system.…”
Section: Photoluminescence Properties Of Si\ti\o\c Nanocomposite Filmssupporting
confidence: 93%
“…They are far above the band gap energy of bulk SiC and SiOC and they suffering from structure defects [3,37]. Song et al reported that the introduction of carbon impurities in the -O\Si\O-network, in the form of -O\C\O-or -Si\C-bonds, can also cause blue emission.…”
Section: Photoluminescence Properties Of Si\ti\o\c Nanocomposite Filmsmentioning
confidence: 99%